Kajian penerimaan dan peranan radio dalam kalangan wanita di Semporna, Sabah - Intan Soliha Ibrahim (Tanjong Malim, 2021)
Kajian penerimaan dan peranan radio dalam kalangan wanita di Semporna, Sabah by Intan Soliha Ibrahim